2018
DOI: 10.1055/s-0038-1676038
|View full text |Cite
|
Sign up to set email alerts
|

Lithopedion in a Geriatric Patient

Abstract: Lithopedion (lithos = rock and paidion = child) is a rare condition that only occurs in 1.5 to 1.8% of extrauterine pregnancies and in 0.00045% of all pregnancies. It consists of an ectopic pregnancy in which the fetus dies but cannot be reabsorbed by the mother's body, which then coats it in a calcium-rich substance. We present the case of a 77-year-old woman with an incidental diagnosis of a lithopedion, which had been retained in her left pelvis for presumably 40 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Though most medical texts reported that there are no classic clinical signs or symptoms [ 2 , 9 ] to aid in the diagnosis of a lithopedion and the majority of cases are discovered during routine imaging or unrelated surgical procedures, the late diagnosis reflects a failure of history taking on the part of the healthcare professionals. In most reported cases, the affected women were aware that they had experienced a pregnancy that did not conclude with the birth of a child or even the passage of blood and tissue to suggest a miscarriage [ 1 7 , 9 – 15 ]. The occurrence of the condition itself reflects lack of access to healthcare, due to multifactorial and intersecting social and structural factors, including poverty, geography, health literacy and awareness, distrust, and discrimination in healthcare.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though most medical texts reported that there are no classic clinical signs or symptoms [ 2 , 9 ] to aid in the diagnosis of a lithopedion and the majority of cases are discovered during routine imaging or unrelated surgical procedures, the late diagnosis reflects a failure of history taking on the part of the healthcare professionals. In most reported cases, the affected women were aware that they had experienced a pregnancy that did not conclude with the birth of a child or even the passage of blood and tissue to suggest a miscarriage [ 1 7 , 9 – 15 ]. The occurrence of the condition itself reflects lack of access to healthcare, due to multifactorial and intersecting social and structural factors, including poverty, geography, health literacy and awareness, distrust, and discrimination in healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer than 300 cases have been reported since the discovery of a case in France in 1582 [ 3 – 6 ]. It occurs in an estimated 1.5 to 1.8% of extrauterine pregnancies and in 0.00045% of all pregnancies [ 7 ]. Cases have been reported in women between the ages of 23 to 100 years with an estimated interval of retention of 4 to 60 years [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When a dead fetus is too big to become reabsorbed by the mother’s body, the immune system treats it as a foreign body. This induces calcium-rich substance deposition on the fetus that will, in due course, turn the fetus body into stone [5].…”
Section: Discussionmentioning
confidence: 99%